Strategy and tactics of soviet state security bodies in the fight against religion and religious communities on the territory of Ukraine - Oksana Vysoven; Висовень Оксана; Natalia Varadi; Вароді Наталія; Váradi Natália; Yuriy Fihurnyi; Юрій Фігурний; Оlha Shakurova; Ольга Шакурова (George Fox University, 2023)
Abstract. The article analyzes the strategy and tactics of state security agencies in the fight against religion and religious Protestant communities on the territory of Soviet Ukraine. The communist totalitarian system, in order to maintain its dominant position in society and fully master the consciousness of its population and influence its spiritual life (the strategic task), shortly after the end of the Second World War, in 1946 in the system of the newly formed Ministry of State Security of the Soviet Union of the Socialist Republics and its republican departments created new special operational departments endowed with extraordinary powers to carry out punitive and repressive and complex preventive actions (the tactical tasks). The “O” (operational) department of the Ministry of State Security of the Ukrainian Soviet Socialist Republic was formed as a part of these functional divisions, which was engaged in the supervision of religious organizations, sects, groups, etc., and this special department “O” was engaged in the planning and implementation of operational work on “agent and operational development of sectarians.” In its work it relied on a number of punitive, repressive, and preventive measures, which were discussed carefully at special meetings, the reports and minutes of which were classified. Only recently the “top secret” seal has been removed from them. The execution of tasks related to the desacralization and liquidation of the prayer houses of the Evangelical Baptist Christians relied on operational commissioners and their agencies. For the successful implementation of tasks related to the liquidation and termination of the prayer houses of Evangelical Baptist Christians, the special services of the State Security Committee combined skillfully punitive, repressive, and preventive methods and systematically involved the cultural, educational, and artistic intelligentsia of Soviet Ukraine.
Keywords: Ukraine; Ukrainians; Christianity; Evangelical Baptist Christians; religion; faith; state security bodies; tactics; strategy; repression; preventive measures